The concepts of funeral rites in the social-humanitarian sciences (Journal of Philosophy Culture and Political Science, 2020)
Death is the end of all the formal functions and life processes of a living organism. When the death of aclose person, the relatives of the deceased feel the need to perform a series of rites in preparation for the funeral.Therefore, death is accompanied by the performance of funeral rites that connect the dead and livingpeople. As can be seen in many studies, funeral rites can be diverse in different societies. A person’s funeralrites come from various beliefs of individuals, social and family groups, which in turn are based on religiousvalues. Besides funeral rites include a set of beliefs and customs used by the culture to commemorate andrespect the deceased from the burial to various memorial rites held in their honor. This research work is ananalysis of foreign sources in the social-humanitarian sciences. The purpose of the article is to determinethe role and place of funeral rites in society. In order to determine opinions in the research of foreign scientistson the search for the Scopus, they searched for documents using the keyword «funeral rites». Theresearch work substantiates the relevance and importance of a theoretical understanding of funeral rites.Key words: funeral rites, death, deceased, culture, family.